2019
DOI: 10.3390/cells8070649
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Phosphoinositides—Versatile Regulators of Genome Functions

Abstract: The many functions of phosphoinositides in cytosolic signaling were extensively studied; however, their activities in the cell nucleus are much less clear. In this review, we summarize data about their nuclear localization and metabolism, and review the available literature on their involvements in chromatin remodeling, gene transcription, and RNA processing. We discuss the molecular mechanisms via which nuclear phosphoinositides, in particular phosphatidylinositol (4,5)-bisphosphate (PI(4,5)P2), modulate nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 145 publications
(230 reference statements)
0
40
0
Order By: Relevance
“…Until now, a plethora of studies have confirmed the existence of PIs and their metabolizing enzymes, i.e., lipases, kinases, and phosphatases, in several subnuclear compartments. This generates a distinct PI pool capable of regulating several essential nuclear processes, such as chromatin remodeling, DNA repair, RNA processing, and gene transcription [1,26,37]. The ability of PI metabolizing enzymes to localize within the same nuclear subcompartments as their respective substrate PI or product confirms their direct involvement in nuclear PI metabolism ( Figure 2).…”
Section: Nuclear Structure and Nuclear Inositidesmentioning
confidence: 81%
See 2 more Smart Citations
“…Until now, a plethora of studies have confirmed the existence of PIs and their metabolizing enzymes, i.e., lipases, kinases, and phosphatases, in several subnuclear compartments. This generates a distinct PI pool capable of regulating several essential nuclear processes, such as chromatin remodeling, DNA repair, RNA processing, and gene transcription [1,26,37]. The ability of PI metabolizing enzymes to localize within the same nuclear subcompartments as their respective substrate PI or product confirms their direct involvement in nuclear PI metabolism ( Figure 2).…”
Section: Nuclear Structure and Nuclear Inositidesmentioning
confidence: 81%
“…Nuclear PtdIns5P regulates chromatin remodeling by interacting with the histone code reader associated with the chromatin complex ING2 (inhibitor of growth protein 2), which is a subunit of the HDAC1 complex (Sin3a-histone deacetylase 1). In particular, PtdIns5P modulates the binding of ING2 to chromatin and also participates in epigenetic gene expression and DNA damage [37,74].…”
Section: Chromatin Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear PIs are critical signal molecules in several nuclear mechanisms such as DNA transcription, pre-mRNA processing or RNA export (Blind et al, 2012;Castano et al, 2019). PI(4,5)P2, labeled by an IgM antibody (2C11), has been found in the nucleus in nonmembrane compartments, nuclear speckles, nucleoli and nuclear lipid islets recently involved in RNA polymerase II transcription (Sobol et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A series of reports have indicated the presence of PI(4,5)P2 in the nucleus (Osborne et al, 2001), particularly in speckles and in nuclear lipid islets (Castano et al, 2019). Nuclear PI(4,5)P2 could be further phosphorylated through the action of inositol phosphate multikinase (IPMK) to produce nuclear PI(3,4,5)P3 (Resnick et al, 2005).…”
Section: Introductionmentioning
confidence: 99%